1986
DOI: 10.1063/1.865698
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of two-stream supersonic turbulent mixing layers

Abstract: Two-stream supersonic turbulent mixing layers with a free-stream Mach number of 2.3 on the high-velocity side are experimentally investigated. A large-scale vortical structure, which has been believed to dominate the development of incompressible mixing layers, is also observed in the present supersonic layers. The spreading rate of the layer is correlated with a velocity ratio of the free streams and a Mach number based on the velocity difference across the layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(55 citation statements)
references
References 6 publications
2
53
0
Order By: Relevance
“…One good [3]: (a) Bogdanoff [7]; Papamoschou and Roshko [40]; (b) Chinzei at al. [9]; (c) Samimy and Elliott [48,49]; -nonlinear regression curve from [3] with method to identify the location of a shock is to use a Schlieren based technique to portray shocks and even more weak discontinuities in the fluid (see ref. [21] for more details about flow visualization).…”
Section: Flow Structures and Shockletsmentioning
confidence: 99%
“…One good [3]: (a) Bogdanoff [7]; Papamoschou and Roshko [40]; (b) Chinzei at al. [9]; (c) Samimy and Elliott [48,49]; -nonlinear regression curve from [3] with method to identify the location of a shock is to use a Schlieren based technique to portray shocks and even more weak discontinuities in the fluid (see ref. [21] for more details about flow visualization).…”
Section: Flow Structures and Shockletsmentioning
confidence: 99%
“…The success of linear stability analyses of these phenomena, at least for subsonic convective Mach numbers, can perhaps also be understood in the same light, since the dominant surviving mode must abide by the same considerations. Papamoschou and Roshko (1988) find that the compressible shear-layer growth rate, when normalized by the corresponding incompressible flow growth rate estimated at the same velocity and density ratio, is well represented as a function of the isentropically estimated convective Mach number only, say, Al(') i.e., Figure 4 includes the data of Papamoschou and Roshko (1988), shear-layer growthrate estimates computed from the earlier data of Chinzei et al (1986) that were processed to estimate M( ) for each of their runs and normalized to the value of 6)l b(MAic )/6(O) at one point (filled circle), the data of Clemens and Mungal (1990), and the data of Hall et al (1991). The smooth curve in Fig.…”
Section: Compressibility Effectsmentioning
confidence: 99%
“…The outcome of the added freedom associated with the data from Chinzei et al (1986) is shown in Figure 23. Each data series in this plot supposedly represents the exact same outcome of one experiment, however they were each extracted from a different source.…”
Section: Apparent Dependence On Mixing Layer Thickness Definitionmentioning
confidence: 99%
“…Take the experimental data published by Chinzei et al (1986) as a case example. Since it was published before the theoretical work of Papamoschou and Roshko (1988), the measured mixing layer growth rates were normalized according to a process that is quite different from the presently accepted incompressible growth rate models.…”
Section: Apparent Dependence On Mixing Layer Thickness Definitionmentioning
confidence: 99%
See 1 more Smart Citation